A Research Paper on Study and Impact of Goods and Service Tax (GST) on Indian Tax Structure - Pandey, Manoj (International Research Journal of Management, IT & Social Sciences (IRJMIS), 2017)
This paper is an analysis of what the impact of GST (Goods and Services Tax) will be on Indian Tax Scenario. The authors have stated with a brief description of the historical scenario of Indian taxation and its tax structure. Then the need arose for the change in tax structure from traditional to GST model. GST has be detailed discuss in this paper by the authors as the background, silent features and the impact of GST in the present tax scenario in India.